Education and Civil Conflict in Nepal - Valente, Christine (Oxford University Press on behalf of the World Bank, 2015)
Between 1996 and 2006, Nepal experienced violent civil conflict as a consequence of a Maoist insurgency, which many argue also brought about an increase in female empowerment. This paper exploits variations in exposure to conflict by birth cohort, survey date, and district to estimate the impact of the insurgency on education outcomes. Overall conflict intensity, measured by conflict casualties, is associated with an increase in female educational attainment, whereas abductions by Maoists, which often targeted school children, have the reverse effect. Male schooling tended to increase more rapidly in areas where the fighting was more intense, but the estimates are smaller in magnitude and more sensitive to specification than estimates for females. Similar results are obtained across different specifications, and robustness checks indicate that these findings are not due to selective migration.